Recovering of fatty acids from soap stock using carbon dioxide - Мольченко, Світлана Миколаївна; Демидов, Ігор Миколайович (Eastern-European Journal of Enterprise Technologies, 2015)
Since the domestic oil and fat industry is characterized by a steady production growth, the amount of waste is constantly increasing, which adversely affects the ecological situation in Ukraine. In particular, these products include soap stock - waste of alkaline refining of vegetable oils, which is a source of fatty acids. Fatty acids are a commodity product, the demand and the cost of which is much higher in the soap stock. The method of recovering fatty acids from the soap stock by carbon dioxide decomposition of their soaps was proposed. The effect of temperature, pressure of carbon dioxide and concentration of the aqueous solution of soap on the decomposition depth was experimentally proved in the paper. Studies have shown that the decomposition process of potassium salts of fatty acids by carbonate acid proceeds at a depth of over 90 %. The resulting fatty acids are well suited for use in many industries. Rational technological parameters were determined, and the approximation model of the process was obtained. It was found that after the decomposition of potassium salts of fatty acids by carbonate acid, fatty acid composition of resulting fatty acids, which was determined by gas-liquid chromatography, changes slightly.